2016
DOI: 10.1515/eng-2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of a skew rolling process for producing a crankshaft preform

Abstract: Abstract:The paper describes a new method for forming a crankshaft preform. The method is based on the skew rolling technique. With this method the part is formed by three tapered rolls rotated with the same velocity and in the same direction. Simultaneously, the rolls either converge or diverge depending on the desired cross section of the product. The numerical modeling enabled determination of the distributions of effective strains, temperatures, and damage function according to the Cockroft -Latham criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…To determine the critical damage value with the proposed rotary compression in cavity test, this process must be numerically modelled by the finite element method. The present analysis is performed with the use of the Simufact.Forming simulation software which was effectively used in previous studies into processes such as cross wedge rolling [43][44][45], Mannesmann piercing [30,46,47], helical rolling of balls [48][49][50], three-roll skew rolling [35,51,52] and other rolling processes [53][54][55][56][57]. performed under laboratory conditions.…”
Section: Fem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the critical damage value with the proposed rotary compression in cavity test, this process must be numerically modelled by the finite element method. The present analysis is performed with the use of the Simufact.Forming simulation software which was effectively used in previous studies into processes such as cross wedge rolling [43][44][45], Mannesmann piercing [30,46,47], helical rolling of balls [48][49][50], three-roll skew rolling [35,51,52] and other rolling processes [53][54][55][56][57]. performed under laboratory conditions.…”
Section: Fem Analysismentioning
confidence: 99%
“…The results demonstrated that the highest damage value occurs in the loci where the balls get separated. The NCL criterion of ductile fracture was also investigated with respect to skew rolling performed in a numerically controlled three-roll mill [35]. Using Simufact.Forming, the authors analysed the rolling process for producing a crankshaft preform.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of the CWR test were performed in Simufact.Forming (v.15, MSC Software Company, Hamburg, Germany). This program was previously used to analyse numerous processes, such as the cross wedge rolling of shafts and axles [ 35 , 36 , 37 ], tube rolling [ 38 , 39 , 40 ], the helical rolling of balls [ 41 , 42 , 43 ], three-roll skew rolling [ 44 , 45 , 46 ] and cross rolling [ 47 , 48 , 49 , 50 , 51 ]. The numerical results of these studies showed high agreement with validating experimental data.…”
Section: Numerical Analysis and Validation Of The Numerical Modelmentioning
confidence: 99%
“…Forming v.15 software, based on FEM. This software was used for analyses of cross-and skew-rolling processes multiple times [41,42,[45][46][47][48][49], and the results of calculations remained compliant with the results of experimental testing.…”
Section: Numerical Analysismentioning
confidence: 99%